PENGARUH KOMBINASI PENGKABUTAN DAN KIPAS ANGIN TERHADAP KONDISI FISIOLOGIS SAPI PERAH PERANAKAN FRIES HOLLAND - , JOHN ARNOLD PALULUNGAN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Fries Holland (FH) dairy cattle from temperate regions. The problems faced by the FH cows while in the wet tropics. Heat stress on dairy cows FH can lead to heat stress. This study aims to determine how much influence combined with the use of sprinkler and fan for pen microclimate condition, physiological condition, and feed consumption. Eight dairy cow lactation to the 4 heads and 4 tails lactation I to III, with an average body weight 409.13 Â± 19.02 kg were divided into two groups (groups A and B). The method used experimental method designed simple balanced crossover design with two treatments and the sprinkler fan (P) and not performed sprinkler and fans (TP) as a control. Implementation of the research was conducted in two phases. Before the first treatment period early stage research conducted to observe the critical points when it is appropriate to do sprinkler. In the pilot study obtained critical points at 10.00, 12.00, 13.00, 14.00, 16.00. At the beginning of treatment sprinkler adaptation to prior period in dairy cows during the first week. The parameters observed were microclimate pen, the physiological and dry matter feed intake. Data were analyzed using analysis of variance. The results obtained microclimate pen conditions namely pen temperature (ÂºC) were significantly different (P â¤ 0.01) in the treated group P and TP respectively 27.91 Â± 1.58 and 29.41 Â± 2.34, humidity enclosure (%) were significantly different (P â¤ 0.05) respectively 73.64 Â± 8.73 and 71.40 Â± 10.35, and Temperature-Humidity Index were significantly different (Pâ¤ 0.01) 76.42 Â± 1.23 and 78.03 Â± 1.99. While the physiological condition, rectal temperature (ÂºC) were significantly different (P â¤ 0.05) in the treated group P and TP respectively 38.58 Â± 0.35 and 38.82 Â± 0.41, pulsus rate (beats/min) significantly different (Pâ¤ 0.05) 64.12 Â± 5.96 and 68.44 Â± 5.85, respiration rate (grunts/min) were significantly different (P â¤ 0.01) and 23.56 Â± 3.36 33.56 Â± 8.02. Treatment and sprinkler fan for 10 minutes can reduce the temperature inside the pen, effectively lowering the Temperature-Humidity Index, as well as rectal temperature, pulsus rate, and respiration rate of cattle, but raise the humidity in the pen. Heat stress experienced by cattle not affect feed intake.